1972
DOI: 10.1002/art.1780150610
|View full text |Cite
|
Sign up to set email alerts
|

The arthritis of leukemia

Abstract: Arthritis related to the primary disease was detected in 10 of 74 (13.5% patients seen primarily for leukemia [2 of 12 patients with acute (16.6% and 8 of 62 (12.4%) with chronic leukemia]. To these were added 18 ad ditional patients previously diagnosed of having arthritis of leukemia.Clinical analyses of 28 patients with arthritis of leukemia showed that the arthritis of acute leukemia was commonly asymmetric, additive, polyarticular and often part of the initial manifestation of the disease. The arthritis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…There have also been a few reports of arthritis secondary to direct tumor invasion in and about joints, and recently the occurrence of acute arthritis due to leukemic infiltration of the synovium has been reported (11,12). T o our knowledge, the following is the first report of metastatic carcinoma to the synovium presenting as an acute arthritis.…”
Section: Metastatic Adenocarcinoma Of Synovium Presenting As An Acutementioning
confidence: 79%
“…There have also been a few reports of arthritis secondary to direct tumor invasion in and about joints, and recently the occurrence of acute arthritis due to leukemic infiltration of the synovium has been reported (11,12). T o our knowledge, the following is the first report of metastatic carcinoma to the synovium presenting as an acute arthritis.…”
Section: Metastatic Adenocarcinoma Of Synovium Presenting As An Acutementioning
confidence: 79%
“…2,3 Several studies concerning the musculoskeletal manifestations of childhood leukemias have shown the importance of these complaints in the clinical presentation and follow-up of these patients. 1,[4][5][6][7][8][9][10] The aims of the present study were to determine retrospectively the frequency and type of occult neoplasias in children who initially presented with musculoskeletal complaints, as well as determining the clinical features and laboratory alterations that can suggest such malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…The specific synovial infiltration by lymphocytic cells represented a more probable mechanism. This has been rarely demonstrated since the availability of synovial fluid examination andlor synovial biopsy (2). The identification of the phenotype of the peripheral blood, skin, and synovial lymphocytes allowed us to state that the arthritis, as well as the skin lesions, constituted a specific localization of CLL in our patient.…”
Section: Figure 2 Focal Area Of Infiltration Of Synovium By Lymphocymentioning
confidence: 82%
“…The identification of the phenotype of the peripheral blood, skin, and synovial lymphocytes allowed us to state that the arthritis, as well as the skin lesions, constituted a specific localization of CLL in our patient. The identification of leukemic cells in synovial fluid (T cell leukemia) has been reported previously (1)(2)(3)(4) …”
Section: Figure 2 Focal Area Of Infiltration Of Synovium By Lymphocymentioning
confidence: 93%